Health effects of job insecurity - Francis Green (IZA World of Labor, 2020)
The fear of unemployment has increased around the world in the wake of Covid-19. Research has shown that job insecurity affects both mental and physical health, though the effects are lower when employees are easily re-employable. The detrimental effects of job insecurity could be partly mitigated if employers improved other aspects of job quality that support better health. But as job insecurity is felt by many more people than just the unemployed, the negative health effects during recessions are multiplied and extend through the majority of the population. This reinforces the need for effective, stabilising macroeconomic policies, most especially at this time of pandemic.
Keywords: I10; J00; J08; 330; job insecurity; employability; unemployment